2018
DOI: 10.3389/fpls.2018.01336
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolic Profiling Indicates Apple Rootstock Genotype-Specific Differences in Primary and Secondary Metabolite Production and Validate Quantitative Contribution From Vegetative Growth

Abstract: Previous reports regarding rhizodeposits from apple roots are limited, and complicated by microbes, which readily colonize root systems and contribute to modify rhizodeposit metabolite composition. This study delineates methods for collection of apple rhizodeposits under axenic conditions, indicates rootstock genotype-specific differences and validates the contributions of vegetative activity to rhizodeposit quantity. Primary and phenolic rhizodeposit metabolites collected from two apple rootstock genotypes, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Additional phenolic compounds play a role in the ARD response, which were shown to accumulate in response to infected soil and may indicate the occurrence of oxidative stress (Henfrey et al, 2015). Especially the dihydrochalcones phloridzin and phloretin have been found highly abundant in apple root exudates and root debris (Hofmann et al, 2009;Emmett et al, 2014;Nicola et al, 2016;Leisso et al, 2018). They act against pathogens and as scavengers of reactive oxygen species (Börner, 1959;Emmett et al, 2014;Henfrey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additional phenolic compounds play a role in the ARD response, which were shown to accumulate in response to infected soil and may indicate the occurrence of oxidative stress (Henfrey et al, 2015). Especially the dihydrochalcones phloridzin and phloretin have been found highly abundant in apple root exudates and root debris (Hofmann et al, 2009;Emmett et al, 2014;Nicola et al, 2016;Leisso et al, 2018). They act against pathogens and as scavengers of reactive oxygen species (Börner, 1959;Emmett et al, 2014;Henfrey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…l ‐asparagine has been shown to be abundantly produced by tree roots contributing to the selection of specific micro‐organisms (Leisso et al . 2018). For the pecan tree, it has been observed that FR stage is characterized by an important cell division followed by the increase of cell size representing specific physiological, metabolic and hormonal requirements for the plant (Yañez et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the Malus accessions, rootstocks with the same GEGV exhibited varied dwar ng ability, for example 'M27' is sometimes referred to as hyper-dwar ng, but 'M26' performs as semi-dwar ng in certain environments [41,42]. Another example is that the GEGV of 'GM256' was relatively large, but the dwar ng potential is much greater than 'MM106' or 'M7' [43,44].…”
Section: Discussionmentioning
confidence: 99%